Lost in the Labyrinth : a Novel - Kindl, Patrice (Boston, Mass., 2005)
Fourteen-year-old Princess Xenodice tries to prevent the death of her half-brother, the Minotaur, at the hands of the Athenian prince, Theseus, who is aided by Icarus, Daedalus, and her sister Ariadne.
Includes bibliographical references (p. 194).
Keywords: Fiction; Ariadne (Greek mythology); Fiction; Theseus (Greek mythology); Fiction; Minotaur (Greek mythology); Fiction; Icarus (Greek mythology); Fiction; Fiction; Daedalus (Greek mythology); Mythology, Greek; Ariadne (Greek mythology); Minotaur (Greek mythology); Juvenile fiction; Juvenile fiction; Juvenile fiction; Theseus (Greek mythology); Mythology, Greek; Daedalus (Greek mythology); Juvenile fiction; Icarus (Greek mythology); Juvenile fiction; Juvenile fiction; Crete (Greece); Juvenile fiction; History; To 67 B.C; Crete (Greece); Fiction; History; To 67 B.C